Conceptual baseline for a global checklist of gypsophytes - Mota Poveda, Juan Francisco; Garrido Becerra, Juan Antonio; Pérez-García, Francisco J.; Salmerón-Sánchez, Esteban; Sánchez-Gómez, Pedro; Merlo, Encarna (Lazaroa, 2016)
Conceptual baseline for a global checklist of gypsophytes